1999
DOI: 10.1002/(sici)1097-4636(199908)46:2<228::aid-jbm12>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Composition and structure of the apatite formed on PET substrates in SBF modified with various ionic activity products

Abstract: An apatite layer was formed on polyethyleneterephthalate (PET) substrates by the following biomimetic process. PET substrates were placed on granular particles of a CaO-SiO2-based glass in simulated body fluid (SBF) with ion concentrations nearly equal to those of human blood plasma to form apatite nuclei on their surfaces (first treatment). They then were soaked in modified SBFs, the ion concentrations of which were changed to give a variation in ionic activity product of apatite (IP), in order to make the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
122
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(137 citation statements)
references
References 26 publications
(37 reference statements)
4
122
0
Order By: Relevance
“…34,35) Moreover, it has been reported that small amount of CO 3 2¹ ions, which is a constituent of the simulated-body fluid, substitute for PO 4 3¹ sites, resulting in Ca 2+ deficiency form. 36,37) As a result, the value of the [Ca]/[P] ratio obtained by ICP-OES was estimated to be lower than that of the stoichiometric value.…”
Section: Resultsmentioning
confidence: 94%
“…34,35) Moreover, it has been reported that small amount of CO 3 2¹ ions, which is a constituent of the simulated-body fluid, substitute for PO 4 3¹ sites, resulting in Ca 2+ deficiency form. 36,37) As a result, the value of the [Ca]/[P] ratio obtained by ICP-OES was estimated to be lower than that of the stoichiometric value.…”
Section: Resultsmentioning
confidence: 94%
“…Ceramics tend to be brittle, present low mechanical strength (in a porous configuration), and unpredictable in vivo degradation/dissolution rates [1,2,6,7]. Polymers on the other hand show reduced osseointegration capabilities, decreased cell-material interactions due to surface hydrophobicity, and excessive ductility for hard tissue replacement applications [1,2,8]. Recent research has been highly focused on the development of polymer-ceramic nanocomposites [1].…”
Section: Introductionmentioning
confidence: 99%
“…This means that the in vivo bone-bonding ability of a given material can be predicted, before animal testing, from the apatite formation on its surface when subjected to this test. Usually, the apatite formed in SBF is carbonate-containing hydroxyapatite similar to bone in composition and structure, but with lower carbonate content than that in the apatite crystals formed in dentin [1] (5.7 wt%) and thus with lower Ca/P molar ratio, which has been attributed to the lower concentration of HCO 3 -ions [54] . The ionic activity product IP of the apatite in an aqueous solution is given by [40,54] : …”
Section: Biomimetic In Vitro Test For Predicting the In Vivo Bioactivitymentioning
confidence: 99%
“…This increases the ionic activity product of the apatite while maintaining the Ca/P molar ratio, and thereby make the apatite nuclei grow more rapidly (growth stage) [54,60,61] . Table 1.1 shows the ion concentrations and the ionic activity products of the apatite in 2×SBF.…”
Section: Biomimetic In Vitro Test For Predicting the In Vivo Bioactivitymentioning
confidence: 99%
See 1 more Smart Citation